2022
DOI: 10.1111/jcmm.17243
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0003945 promotes progression of hepatocellular carcinoma by mediating miR‐34c‐5p/LGR4/β‐catenin axis activity

Abstract: Accumulating evidence suggests that circular RNAs (circRNAs) play essential roles in regulating cancer progression, but many circRNAs in hepatocellular carcinoma (HCC) remain unknown. Dysregulated circRNAs in HCC were identified through bioinformatics analysis of Gene Expression Omnibus data sets. Quantitative real-time PCR (qRT-PCR), Sanger sequencing, RNase R digestion and actinomycin D treatment were conducted to confirm the characterization of circRNAs. CCK-8, wound-healing and Transwell assays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…LGR4 overexpression could promote the processes of proliferation, migration, and invasion. Although the study indicated that Hsa_circ_0003945 could regulate the miR-34c-5p/LGR4/β-catenin axis to promote the progression of hepatocellular carcinoma [16], the exact role of LGR4 is still unclear. Mechanistically, LGR4 can activate wnt/β-catenin signaling in many diseases [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGR4 overexpression could promote the processes of proliferation, migration, and invasion. Although the study indicated that Hsa_circ_0003945 could regulate the miR-34c-5p/LGR4/β-catenin axis to promote the progression of hepatocellular carcinoma [16], the exact role of LGR4 is still unclear. Mechanistically, LGR4 can activate wnt/β-catenin signaling in many diseases [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study indicated that Hsa_circ_0003945 could regulate the miR-34c-5p/LGR4/β-catenin axis to promote the progression of hepatocellular carcinoma [16], the exact role of LGR4 is still unclear. Mechanistically, LGR4 can activate wnt/β-catenin signaling in many diseases [16][17][18]. So, we detected the expression of catenin through immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 acts as specific biomarker of cellular proliferation, regulated through cell cycle-dependent transcription and protein degradation processes ( 76 , 77 ). Notably, overexpression of circ_0003945 was significantly associated with enhanced cellular of Ki-67 levels in NSCLC and HCC cells, implicating its roles in tumor cell proliferation ( 41 , 43 ). In vivo , xenograft assays in mice had verified that stable knockdown of circ_0003945 led to reduced tumor volumes and weights compared matched controls.…”
Section: The Biological Functions and Mechanisms Of Circ_0003945 In T...mentioning
confidence: 98%
“…Circ-102,166, a circRNA encoded by the TEX2 gene locus, inhibited HCC development by binding with miR-182 and miR-184 to regulate the expression of their downstream targets, including FOXO3a, MTSS1, SOX7, p-RB and c-MYC (Li R. et al, 2020). CircLIFR has also been identified to function as a tumor suppressor, suppressing the proliferation and invasion of HCC cells through the miR-624-5p/GSK-3β axis (Yang L. et al, 2022).…”
Section: Circrnas Regulate Hcc Cell Proliferationmentioning
confidence: 99%